Sistem Informasi Penjualan pada Karo Rumah Mode di Simalingkar berbasis Web - Sinaga, Mariani; Malau, Emerson P. (LPPM UNIKA Santo Thomas Medan, 2018)
This study discusses the web-based sales information system at the Rumah Mode Karo store which has a collection of different men's and women's clothing products for sale. In addition to selling clothing collections, karo fashion houses also sell Tupperware. Karo Rumah Mode currently still sells directly and does not have a sales information system so that it causes problems such as recording the Karo Rumah Mode sales transaction data still manually, the store is difficult to control all products that have been sold and those that have not been sold, nor is the store know how much stock is still available for each type of product, who receives money on the sale of a product is also not well-documented and clear. Then from the problems that arise the proposed solution to overcome this problem is to build a sales information system that uses the PHP programming language and MYSQL as the database. The goal is a web-based information system that is built can make sales both online and directly in the store and facilitate users in sales transactions, report inventory and receipt of money against sales transactions are well-documented and clear. The method used in this study is literature study and interviews / case studies at fashion house karo stores.